2019
DOI: 10.1109/access.2019.2960077
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Inspiratory Muscle Neuromechanical Coupling During Inspiratory Threshold Loading

Abstract: Diaphragm neuromechanical coupling (NMC), which reflects the efficiency of conversion of neural activation to transdiaphragmatic pressure (P di), is increasingly recognized to be a useful clinical index of diaphragm function and respiratory mechanics in neuromuscular weakness and cardiorespiratory disease. However, the current gold standard assessment of diaphragm NMC requires invasive measurements of P di and crural diaphragm electromyography (oesEMG di), which complicates the measurement of diaphragm NMC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…Inspiratory threshold loading protocols are associated with changes in breathing pattern and, particularly, with an increase of tidal volume with respect to baseline in healthy subjects [22], [27], [28], [37]. The increase in ∆bioZ can only be observed in the mild group of which the median values were higher than median values of the other two groups (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Inspiratory threshold loading protocols are associated with changes in breathing pattern and, particularly, with an increase of tidal volume with respect to baseline in healthy subjects [22], [27], [28], [37]. The increase in ∆bioZ can only be observed in the mild group of which the median values were higher than median values of the other two groups (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, clinical evidence is still limited, only a few studies have investigated and showed the applicability of the use of bioimpedance in respiratory diseases, focusing on infants suffering from reduced lung function [14]- [16]. Other noninvasive measurements such as surface electromyography (sEMG) and surface mechanomyography (sMMG) have been investigated for assessment of muscle function in healthy and diseased state [9], [10], [17]- [22]. These studies showed strong correlations between sEMG and sMMG and classical invasive measurements of respiratory muscle function [17]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…All recordings were obtained from 12 healthy subjects, including 6 male and 6 female, with no medical history of neuromuscular or cardiorespiratory disease and with the following characteristics (median (interquartile range)): age 33 (30–39) years, body mass index (BMI) 22.2 (20.6–24.2) kg/m 2 , forced expiratory volume in 1 second 98% (95–106%) % of predicted, and forced expiratory volume in 1 second/forced vital capacity 82% (74–84%) % of predicted [ 19 ]. Written consent was provided by all subjects prior to study participation.…”
Section: Methodsmentioning
confidence: 99%
“…In the respiratory system, sMMG and pressure represent different mechanical states of inspiratory muscles, the latter being a more global measure of respiratory muscle mechanical output. We have recently used sMMG and sEMG measurements from lower chest wall intercostal spaces (sMMG lic and sEMG lic , respectively) to provide noninvasive indices of lower chest wall inspiratory muscle NMC [ 19 ], which did not change significantly with increasing inspiratory load due to the linear relationship between sMMG lic and sEMG lic measurements. Measurements of sMMG lic have also been used, in combination with measurements of mouth pressure (P mo ), to calculate the mechanical efficiency (MEff) of lower chest wall inspiratory muscles, that is the transformation of muscle mechanical activation into pressure generation, in healthy subjects and patients with chronic obstructive pulmonary disease (COPD) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation